La participación ciudadana y su incidencia en la toma de decisiones en el presupuesto participativo en el GAD del cantón Chone - Barberán Palma, Belky Lisseth (2022)
The present research work was carried out with the objective of knowing citizen participation and its incidence in the decision-making of the participatory budget of the GAD of the Chone canton. In addition, scientific theories were established that provided support in the investigation, as well as deductive, inductive and synthetic - analytical methods that allowed the efficient and effective development of the actions under study, also, through the interview that was conducted with the director of citizen participation, it was possible to know the current situation of the procedures that they carry out in conjunction with the citizenry. In the same way, the survey was applied to 382 citizens, whose most relevant results were the lack of knowledge of the ordinance; Ignorance of the citizen participation unit by the citizens and limited communication of the calls made by the citizen participation unit of the GAD of Chone before the citizens. With the results obtained above, it is said that the scientific information on citizen participation contributed to designing a SWOT matrix where each positive and negative aspect of the management can be observed, and, finally, an improvement plan was proposed that will contribute to the institution in a positive way to improve its objectives and goals and contribute to the development of the city.